2008
DOI: 10.1200/jco.2007.12.2689
|View full text |Cite
|
Sign up to set email alerts
|

Phase III Trial Comparing Carboplatin, Paclitaxel, and Bexarotene With Carboplatin and Paclitaxel in Chemotherapy-Naïve Patients With Advanced or Metastatic Non–Small-Cell Lung Cancer: SPIRIT II

Abstract: Purpose The purpose of this study was to determine whether addition of the synthetic rexinoid bexarotene (Targretin; Eisai Inc, Woodcliff Lake, NJ) to standard first-line carboplatin and paclitaxel therapy provides additional survival benefit in patients with advanced non–small-cell lung cancer (NSCLC). Patients and Methods Patients with stage IIIB disease with pleural effusion, or stage IV NSCLC and Eastern Cooperative Oncology Group performance status 0 to 1, were randomly assigned to bexarotene 400 mg/m2/d … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
49
0
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(52 citation statements)
references
References 13 publications
2
49
0
1
Order By: Relevance
“…An important finding of the Dmitrovsky group's phase II trial was a significant survival benefit associated with bexarotene-induced hypertriglyceridemia (P ¼ 0.001), consistent with prior studies of bexarotene alone or combined with chemotherapy in NSCLC (4,5,19). Hypertriglyceridemia generally developed within 2 to 4 weeks in all these studies, and, long known in association with retinoids such as 13cRA (20), it does not seem to have adverse clinical effects.…”
Section: Introductionsupporting
confidence: 73%
See 1 more Smart Citation
“…An important finding of the Dmitrovsky group's phase II trial was a significant survival benefit associated with bexarotene-induced hypertriglyceridemia (P ¼ 0.001), consistent with prior studies of bexarotene alone or combined with chemotherapy in NSCLC (4,5,19). Hypertriglyceridemia generally developed within 2 to 4 weeks in all these studies, and, long known in association with retinoids such as 13cRA (20), it does not seem to have adverse clinical effects.…”
Section: Introductionsupporting
confidence: 73%
“…Chemotherapy in general for this disease has been limited by toxicity and a lack of specificity and did not improve when combined with the epidermal growth factor receptor (EGFR) inhibitor erlotinib (2,3) or with the rexinoid bexarotene (4,5). Lung cancer chemoprevention has foundered heretofore for a variety of reasons, although very recent clinical data suggest promise in this setting (6).…”
Section: Introductionmentioning
confidence: 99%
“…Bexarotene is currently the only rexinoid approved by the FDA, for treatment of cutaneous T-cell lymphoma. Notably, bexarotene, either alone or in combination with erlotinib and various chemotherapeutic agents, has been tested in a variety of clinical trials for lung cancer (4)(5)(6)(7)(8)(9). Although bexarotene failed to increase overall survival as a single agent, subsets of patients responded to the drug, with highgrade hypertriglyceridemia identified as a biomarker of efficacy.…”
Section: Introductionmentioning
confidence: 99%
“…A recent clinical trial with RXR ligand as a single therapeutic regimen has shown a favorable clinical outcome with mild toxicity for a selected subgroup of advanced lung cancer patients (11), suggesting that the downstream target of RXR would provide a mechanistic understanding of the anticancer effect of RXR ligands. One of the affected downstream pathways by liganded RXR is the p21 through RXR homodimer bindings to the two sequential RXREs, which overlap with an RARE (Fig.…”
Section: Implications and Questionsmentioning
confidence: 99%
“…11). However, rexinoid therapy significantly improved the overall survival in certain patient subgroups (i.e., males, smokers, and patients with stage IV disease) compared with the control group (11). The molecular mechanisms underlying this subgroup-dependent response and the molecular basis of rexinoid resistance remains to be understood.…”
Section: Introductionmentioning
confidence: 97%